(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes in detail the manifestations of peptic ulcer of the stomach and duodenum, the morphological basis, and the physiology of origin. The main focus is on prevention and treatment using traditional medicine methods based on the study of the causes of the disease. The side effects of drugs used in medicine today on this disease were analyzed. The activity of enzymes (ALT, AST, IF and GGT) in the liver of rats in the experiment was determined as biomarkers for determining the biological activity of FA “Asprulans”, made on the basis of walnut and peach leaves with a high content of antioxidants. The results of disease correction using Asprulans FA were analyzed and appropriate conclusions were drawn.